2016
DOI: 10.3389/fpsyt.2016.00030
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Tegmental Area Afferents and Drug-Dependent Behaviors

Abstract: Drug-related behaviors in both humans and rodents are commonly thought to arise from aberrant learning processes. Preclinical studies demonstrate that the acquisition and expression of many drug-dependent behaviors involves the ventral tegmental area (VTA), a midbrain structure comprised of dopamine, GABA, and glutamate neurons. Drug experience alters the excitatory and inhibitory synaptic input onto VTA dopamine neurons, suggesting a critical role for VTA afferents in mediating the effects of drugs. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 237 publications
(280 reference statements)
1
25
0
Order By: Relevance
“…followed the same protocol and reported approximately 25% of NeuN-positive cells were also TH-positive 30 . The exact percentage of TH-positive neurons in the VTA is not known, but is speculated to be about 50–60% 31 ; therefore, we considered the estimated 25–30% of TH-positive neurons after fluorescent-activated cell sorting (FACS) to be adequate for the suggested experiment, consistent with other studies 30 , 32 . There was no significant difference in the number of collected DA neurons per VTA between the treatment groups since the saline-treated and nicotine-treated groups had 27.1% ± 3.7% and 28.5% ± 3.1% double-positive neurons from the total NeuN-positive neurons, respectively.…”
Section: Resultssupporting
confidence: 63%
“…followed the same protocol and reported approximately 25% of NeuN-positive cells were also TH-positive 30 . The exact percentage of TH-positive neurons in the VTA is not known, but is speculated to be about 50–60% 31 ; therefore, we considered the estimated 25–30% of TH-positive neurons after fluorescent-activated cell sorting (FACS) to be adequate for the suggested experiment, consistent with other studies 30 , 32 . There was no significant difference in the number of collected DA neurons per VTA between the treatment groups since the saline-treated and nicotine-treated groups had 27.1% ± 3.7% and 28.5% ± 3.1% double-positive neurons from the total NeuN-positive neurons, respectively.…”
Section: Resultssupporting
confidence: 63%
“…The posterior VTA was targeted due to its proposed role in the rewarding effects of many drugs of abuse [40]. However, due to the heterogeneity in GABAergic inputs to and local interneurons within the VTA [3], it is possible the extracellular GABA concentration may differ between subregions within the VTA. For example, a recent study used low-flow push–pull perfusion to measure the extracellular concentration of multiple neurotransmitters with high spatial resolution [65].…”
Section: Discussionmentioning
confidence: 99%
“…The ventral tegmental area (VTA) is a brain region involved in reward processing, aversion and the development of some drug-dependent behaviors [13]. Inhibitory signaling in the VTA is altered by many drugs of abuse and γ-aminobutyric acid (GABA) neurons have an emerging role in regulating reward and aversive learning [46].…”
Section: Introductionmentioning
confidence: 99%
“…Addiction to substances of abuse is thought to be caused by functional changes in a neural network implicated in emotions, learning and cognitive control (Robinson & Berridge, ; Goldstein & Volkow, ; Koob, ; Piazza & Deroche‐Gamonet, ; Volkow & Morales, ; Everitt & Robbins, ) as a result of prolonged exposure to drugs (Deroche‐Gamonet et al ., ; Vanderschuren & Everitt, ; Pelloux et al ., ; Jonkman et al ., ; Vanderschuren & Ahmed, ; Limpens et al ., ). Brain structures widely implicated in addiction include the prefrontal cortex, striatum, amygdala and the ventral tegmental area (VTA) (Jentsch & Taylor, ; Feil et al ., ; Koob & Volkow, ; Hearing et al ., ; Everitt & Robbins, ; Oliva & Wanat, ). More recently, studies have begun to investigate the role of the lateral habenula (LHb) in addictive behavior, and it has been suggested that this structure is important for the aversive aspects of drug intake (Jhou et al ., ; Meye et al ., ; Shelton et al ., ).…”
Section: Introductionmentioning
confidence: 99%